New and personalized ventilatory strategies in patients with COVID-19 - Rodrigues de Moraes, Lucas; Robba, Chiara; Battaglini, Denise; Pelosi, Paolo; Rocco, Patricia R. M.; Silva, Pedro Leme (Frontiers in Medicine, 2023)
Coronavirus disease (COVID-19) is caused by the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) virus and may lead to severe respiratory failure and the need for mechanical ventilation (MV). At hospital admission, patients can present with severe hypoxemia and dyspnea requiring increasingly aggressive MV strategies according to the clinical severity: noninvasive respiratory support (NRS), MV, and the use of rescue strategies such as extracorporeal membrane oxygenation (ECMO). Among NRS strategies, new tools have been adopted for critically ill patients, with advantages and disadvantages that need to be further elucidated. Advances in the field of lung imaging have allowed better understanding of the disease, not only the pathophysiology of COVID-19 but also the consequences of ventilatory strategies. In cases of refractory hypoxemia, the use of ECMO has been advocated and knowledge on handling and how to personalize strategies have increased during the pandemic. The aims of the present review are to: (1) discuss the evidence on different devices and strategies under NRS; (2) discuss new and personalized management under MV based on the pathophysiology of COVID-19; and (3) contextualize the use of rescue strategies such as ECMO in critically ill patients with COVID-19.